Distribusi Barang Melalui Asia Tenggara Yang Berlatar Politis - Yusmaini Eriawati (Balai Arkeologi Yogyakarta, 1994)
Textual data from local historical sources in Indonesia in the form of inscriptions and literary works can be said to have provided a fairly complete explanation of various aspects of life in the past. It would be more complete if the data were combined and compared with data from foreign written sources, from China, Europe and Arabia. Most of the research that concerns the distribution or exchange of goods, especially in the Southeast Asia region, is always related to the economic aspect, namely trade. Several descriptions of Chinese foreign sources indicate another aspect underlying the exchange (delivery) of goods between China and countries in the southern sea region, namely the exchange of goods for political purposes.